2000
DOI: 10.1007/s004170000178
|View full text |Cite
|
Sign up to set email alerts
|

Primitive neuroectodermal tumor of the orbit in a 5-year-old girl with microphthalmia

Abstract: This case is the first reported intraconal PNET of the orbit, and the first orbital case that expresses the MIC2 gene. In spite of the aggressive malignant features of peripheral PNET, the orbital variety seems to be the least aggressive since most of the reported patients are still alive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Five of the published patients's results, and the present case, have been treated with such a therapeutic combination, and the survival time has been found to be longer than 30 months for all patients,7 10 11 15 except for that of one patient, which was 17 months 5…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Five of the published patients's results, and the present case, have been treated with such a therapeutic combination, and the survival time has been found to be longer than 30 months for all patients,7 10 11 15 except for that of one patient, which was 17 months 5…”
Section: Discussionmentioning
confidence: 51%
“…When performed, surgery should remove the tumour completely, but this might be technically difficult. Chemotherapy with or without radiotherapy is considered by many authors to be the best additional treatment 3 5 8 10 11 13 15 38. Recent studies suggest that a multidiscipline treatment including systemic chemotherapy and surgery could prolong survival in patients with Ewing sarcoma family tumours 39.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the orbital variety of malignant pPNET-peripheral neuroepithelioma has been linked to a less aggressive behavior; in eight reported cases, none of the tumors exhibited systemic metastatic spread, and only one patient died of disease. 34 Despite the lack of long followup in our series, it is notable that all five patients are alive, and only one patient has had metastatic disease develop. A relatively less dismal outcome for patients with head and neck malignant pPNET-peripheral neuroepithelioma can be also inferred from our review; of 37 patients with available information 27 (73%) were reported as alive and 10 (27%) died of disease.…”
Section: Discussionmentioning
confidence: 66%
“…All are characterized by translocations involving the EWS gene at 22q12, usually the translocation t(11;22)(q24;12). [78] Histopathological appearances of a small, round, dark blue cell tumor with monotonous, highly cellular pattern, pseudo-rosette formation and strong membrane positivity for the MIC-2 gene product in IHC is the hallmark for diagnosis of pPNET. In some cases they are NSE, synaptophysin and S-100-positive.…”
Section: Discussionmentioning
confidence: 99%
“…[8] had reported an orbital, intraconal pPNET in a five-year-old child with microphthalmia since birth. Orbitotomy was performed and a large, polycystic, retroscleral, intraconal tumor was removed.…”
Section: Discussionmentioning
confidence: 99%